Caracterización fisicoquímica y reológica de miel de abeja comercializada en la feria agroindustrial de Huánuco - Ramos R, Miriam (2014)
Several physicochemical (Humidity, acidity, pH, conductivity, reducing sugars, hydroxymethylfurfural, soluble solids and refraction index), sensory and rheological properties of three samples of honey bee from different origins (Daga, Illatupha and Linderos) obtained in an Agroindustrial Fair were studied in order to characterize them monthly during five months of storage for physicochemical and sensory analysis and six months for rheological analysis. Average values for Humidity varied from 14.20 to 13.34, pH was kept stable (4.05 a 4.06), acidity increased from 45.50 to 55.11 mEq, conductivity changed from 813.78 to 1092.33µs/cm, reducing sugars varied from 83.09 to 84.97 g/100g, Hydroxymethylfurfural (HMF) from 36.79 to 54.76 mg/Kg, solublesolids from 78.83 to 83.80 °Brix, refraction index changed around 1.49 to 1.50, at the beginning and after five month of storage respectively. Daga’s honey acidity changed from 70.5 to 72.36, and Illatupha honey acidity from 40.0 to 42.83 (meq. per kilogram) since the beginning to the end respectively; for Linderos’s honey, the HMF content varied from 85.63 to 107.75 mg/Kg; these measured values in both, acidity and HMF, revealedthat these values are over the established range of current regulations. There were no significant differences in sensorial analysis of the three samples since the beginning and after five months, however Linderos’s honey got highest preference. Rheological behavior of the three honeys was carried out under the temperatures ranging 23±2°C. The analysis revealed most pseudoplastic behavior of the tested honey samples at start and after six months. The viscosity (µ) and consistency index parameter (k) increasedat different grades with increase in time.